2016
DOI: 10.1136/thoraxjnl-2015-207686
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetes control status on treatment response in pulmonary tuberculosis: a prospective study

Abstract: Uncontrolled diabetes is an independent risk factor for poor treatment response in PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 29 publications
5
50
2
Order By: Relevance
“… in India suggested 14.8% PTB and 20.2% smear‐positive TB linked to DM. Studies from south India (25.0%, 29.0% and 44.0% in Tamilnadu, Pondicherry and Kerala, respectively), Pakistan (25.9%), South Korea (23.8%) and Mexico (29.6%) have reported substantially higher DM prevalence than our report . The diverse DM prevalence in different settings may also attributed to the methods of DM diagnosis, outcome definitions and failure to control for important confounders.…”
Section: Discussioncontrasting
confidence: 75%
“… in India suggested 14.8% PTB and 20.2% smear‐positive TB linked to DM. Studies from south India (25.0%, 29.0% and 44.0% in Tamilnadu, Pondicherry and Kerala, respectively), Pakistan (25.9%), South Korea (23.8%) and Mexico (29.6%) have reported substantially higher DM prevalence than our report . The diverse DM prevalence in different settings may also attributed to the methods of DM diagnosis, outcome definitions and failure to control for important confounders.…”
Section: Discussioncontrasting
confidence: 75%
“…In previous reports, the presence of cavities was associated with HbA1C level, and cavity formation was significantly more common in uncontrolled DM patients than in non-DM patients [19,31]. Also, whereas a previous study showed no significant difference in the formation of cavities between non-DM and well-controlled DM in TB patients [19], there has yet to be any corresponding reports on NTM. In our study, there was no significant difference in the status of diabetes control among DM patients in NTM and TB patients.…”
Section: Discussionmentioning
confidence: 95%
“…Age, gender, body mass index (BMI), smoking history, previous TB history, underlying disease (DM, the status of diabetes control, malignancy, and chronic obstructive pulmonary disease [COPD]), initial symptoms (cough, sputum, hemoptysis, dyspnea, or fever), and laboratory findings (albumin, white blood cell [WBC], C-reactive protein [CRP]) of all the study patients were recorded. Uncontrolled DM was defined as glycated hemoglobin (HbA1C) level ≤ 7.0% [19]. NTM pathogens proven in culture were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is an important co-morbidity in patients with tuberculosis (TB) because it can increase the risk of active TB [3, 4], have severe clinical manifestations, and cause worse outcomes [5, 6]. DM can also cause dysregulation of the immune system, resulting in altered levels of cytokines and chemokines [7, 8].…”
Section: Introductionmentioning
confidence: 99%